2018
DOI: 10.1186/s40248-017-0114-3
|View full text |Cite
|
Sign up to set email alerts
|

Home exercise improves the quality of sleep and daytime sleepiness of elderlies: a randomized controlled trial

Abstract: BackgroundAging causes physiological changes which affect the quality of sleep. Supervised physical exercise is an important therapeutic resource to improve the sleep of the elderlies, however there is a low adherence to those type of programs, so it is necessary to implement an exercise program which is feasible and effective. The study aimed to test the hypothesis that a semi-supervised home exercise program, improves sleep quality and daytime sleepiness of elderlies of the community who present poor sleep q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 36 publications
4
27
2
1
Order By: Relevance
“…The findings of the current work have verified that the sleep quality was not altered when the Berlin Questionnaire was used. This result agrees with Brandão et al [53] who have reported that home exercise does not alter the risk to OSA when the same questionnaire was used.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the current work have verified that the sleep quality was not altered when the Berlin Questionnaire was used. This result agrees with Brandão et al [53] who have reported that home exercise does not alter the risk to OSA when the same questionnaire was used.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Reid et al [52] have verified that moderate aerobic PE improved the sleep quality of sedentary adults considering the PSQI and the ESS. Brandão et al [53] have reported that home exercise improves the quality of sleep and daytime sleepiness of elderlies considering, respectively, the PSQI and the ESS.…”
Section: Discussionmentioning
confidence: 99%
“…Total duration of exercise programs ranged from 2 to 12 months with respective frequency and length of sessions. Of these 22 articles, subjective sleep quality was assessed in 14 studies with the PSQI scale, in four studied with the ISI scale ( 20 , 25 , 27 , 43 ), and in two studies with the ESS scale ( 28 , 33 ). Six studies evaluated physiological sleep conditions by the use of Actigraphy ( 27 29 , 35 , 39 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Brandão et al [43], in a group of 131 elderly, the average ESS point value was 8.6 ± 2.8. In another study by Brandão et al [44], 40 seniors (30.5%) reported excessive daytime sleepiness as measured by the ESS, while the average ESS score in the study group was 8.32 ± 2.2 points, which is not an indication of excessive daytime sleepiness, similar to other studies [45, 46].…”
Section: Discussionmentioning
confidence: 99%